Public expenditure on agriculture and its impact - Benin, Samuel (International Food Policy Research Institute, 2019)
This chapter examines past patterns of public spending on agriculture in Ghana, and asks whether Ghana has invested enough resources in agriculture and how the patterns of investment in the sector have impacted agricultural productivity growth.